Memories of Serbian Victims under Bulgarian occupation in Leskovački glasnik (1915-1918) - Antić, Dejan D. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The Serbian army was forced to retreat towards Metohija and Albania eventually due to the armed aggression and attacks from the north and east in October 1915 by the united forces of the German and Austro-Hungarian units against the Kingdom of Serbia. Together with the army, the monarch, executive and legislative branch, intellectuals and civilians also retreated, not wanting to fall in the hands of the incoming army formations of the Central Powers. Following the retreat of the government and army bodies, the territory of the Kingdom of Serbia found itself under the control of the enemy forces, which started the 3-year period of occupation. The subject of this paper are the texts written by the newspaper called Leskovački glasnik (Leskovac Messenger) in the period between World War I and World War II, which dealt with the sufferings of the Serbian civilians in the Bulgarian occupied zone from 1915 to 1918. Special attention is paid to the Leskovački glasnik’s reports about marking the anniversary of the Bulgarian terror and killings of Serbs, about opening and consecration of memorials, about the heroic deeds and the tragic destiny of the people in south Serbia.
Keywords: memories; occupation; Kingdom of Serbia; Bulgarians; Leskovački glasnik